Fingerprint identification: (do fingerprints lie?) - Leyaley, Julienne S. (Quezon City : Wisemans Books Trading, Inc., 2021)
"This book discusses the importance of fingerprints fingerprints in the field of police work. This also presents the techniques on how to process the crime scene involving fingerprints and how to lift latent prints."
Includes bibliographical references.
English text.
Keywords: Fingerprints--Identification